Efektivitas Intervensi Self-Compassion Writing Terhadap Stres dan Well-Being Mahasiswa - Aini, Qurrota; Maulana, Herdiyan; Ariyani, Mira (Journal of Research and Measurement in Psychology: JPPP, 2025)
Addressing mental health issues among Indonesian college students is crucial due to the high prevalence of stress. Students face significant stress from academic workloads, challenging assignments, and financial constraints, which can lead to long-term consequences such as academic decline, diminished quality of life, and social dysfunction. Despite this need, universities often lack sufficient mental health support due to social-psychological barriers and resource limitations. While individuals may independently manage early-stage stress symptoms—referred to as coping—students require empirically validated, effective, and accessible coping strategies. One emerging coping model is instilling self-compassion (SC), which involves showing unconditional kindness to oneself when facing pressure. SC can be delivered through writing interventions as a means of self-help. Data were collected from 32 student participants using a within-subject experimental design to measure stress (Perceived Stress Scale/PSS), well-being (Satisfaction with Life/SWLS), and self-compassion (Self-Compassion Scale/SCS). The data analysis technique used was Repeated Measure ANOVA. The study results showed that the self-compassion writing intervention was not effective in reducing stress, nor was it effective in improving well-being and self-compassion. Keywords: College student, Coping strategy model, Self-compassion writing, Stress, Well-being